Construção de fantomas homogêneos pediátricos de crãnio e tórax para otimização de imagens em radiografia computadorizada - Alves, Allan Felipe Fattori [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this work was to optimize computed radiography techniques of skull and chest for pediatric patients between 1 and 5 years old. To achieve this goal, pediatric homogenous phantoms were developed from retrospective computed tomography (CT) scans. In this procedure, a computational algorithm was used to quantify the average thickness of biological tissue (lung, fat, soft and bone tissue) present on the anatomic region under study. These thicknesses were converted into simulators materials (Lucite and aluminum) to build the homogeneous phantoms of skull and chest. The relative uncertainties in the quantification process of skull examinations were 3.5% for soft tissue and 9.5% for bone tissue. In the chest examination, the relative uncertainties were 19.4% for lung tissue, 13.0% for soft tissue and 20.0% for bone tissue. The chest phantom was constructed with 7.3 cm of lucite distributed in four plates of the same thickness (15.0 x 15.0 x 1.82) cm³ arranged in two pairs, separated by a spacing of 2.86 cm of air. Two aluminum plates (15.0 x 15.0 x 0.13) cm³ and (15.0 x 15.0 x 0.10) mm³ were inserted, respectively, between the upper and lower pairs of Lucite. The skull phantom was constructed with 11.98 cm of Lucite distributed in five plates of the same thickness (15.0 x 15.0 x 2.33) cm³. Two aluminum plates (15.0 x 15.0 x 0.16) cm³ and (15.0 x 15.0 x 0.12) cm³ were inserted between the upper and lower pairs of Lucite. These homogeneous phantoms were used in the optimization process for CR systems to determine test techniques (kVp and mAs combination), which produced levels of exposure around 1.96 lgM. The test images, obtained in this process, were used in the determination of physical parameters such as the effective detective quantum efficiency (eDQE) and contrast-detail. These parameters were associated with the optimal images of skull and chest for adult patients obtained in previous studies. Optimal images obtained in ...

Este trabalho teve como objetivo a otimização de imagens de radiografia computadorizada (CR, do inglês, computed radiography) de crânio e tórax de pacientes pediátricos entre 1 e 5 anos de idade. Para atingir esse objetivo foram desenvolvidos fantomas homogêneos pediátricos, que simularam a faixa etária em estudo, a partir de exames retrospectivos de tomografia computadorizada (CT, do inglês, computed tomography). Nesse procedimento foi utilizado um algoritmo computacional para quantificar as espessuras médias de tecidos biológicos (tecido pulmonar, adiposo, mole e ósseo) presentes nas regiões anatômicas em estudo. Essas espessuras foram convertidas em materiais simuladores (lucite e alumínio) de modo a compor os fantomas homogêneos de crânio e tórax. As incertezas relativas no processo de quantificação dos exames de crânio foram de 3,5% para tecido mole e 9,5% para tecido ósseo. Na quantificação dos exames de tórax a incerteza relativa foi de 19,4% para o tecido pulmonar, 13,0% para o tecido mole e 20,0% para o tecido ósseo. O fantoma de tórax foi construído com 7,3 cm de lucite distribuídos em 4 placas de mesma espessura (15,0 x 15,0 x 1,82) cm³ arranjadas em dois pares, separadas por um espaçamento de ar de 2,86 cm. Duas placas de alumínio de (15,0 x 15,0 x 0,13) cm³ e (150,0 x 150,0 x 1,0) mm³ foram inseridas, respetivamente, entre os pares superior e inferior de lucite. O fantoma de crânio foi construído com 11,98 cm de lucite distribuídos em cinco placas de mesma espessura (15,0 x 15,0 x 2,33) cm³. Duas placas de alumínio (15,0 x 15,0 x 0,16) cm³ e (15,0 x 15,0 x 0,12) cm³ foram inseridas, respectivamente, entre os pares superior e inferior de lucite. Os fantomas homogêneos foram utilizados no processo de otimização de imagens em sistemas CR, para calibração do feixe de raios X. No processo de calibração foram determinadas técnicas-teste (combinação kVp e mAs), que produziram índices de ...
Keywords: Diagnóstico por imagem; Radiografia; Torax - Radiografia; Cranio - Radiografia; Chest - Radiography